Isolation and characterization of rabbit caecal pectinolytic bacteria - Sirotek, K; Marounek, M; Rada, V; Benda, V (Folia microbiologica, 2001)
Two hundred and thirty colonies from the caecal contents of six rabbits were picked up and, after a 2-d incubation, were microscopically characterized using Gram staining. Large Gram-negative (34%) and small Gram-negative (30%) irregular rods, Gram-negative (27%) and Gram-positive (8%) cocci were found. Eleven isolates (Bacteroides ovatus (6 strains), B. thetaiotamicron, B. caccae, B. stercoris, B. capillosus and Capnocytophaga ochracea) were identified using commercial tests for measuring their catalase activity, metabolite production, etc., and testing their growth in 20% bile. Bacteria belonging to the genus Bacteroides were demonstrated to be the principal pectinolytic organisms in the rabbit caecum.
Keywords: králíci; Rabbits; polygalakturonasa; Pectins; Polysaccharide-Lyases; Bacteria; cékum; polysacharid-lyasy; Animals; Bacteroides; pektiny; Polygalacturonase; zvířata; Cecum